Phylogenetic study of acanthamoeba isolated from stray animal corneas (cats & dogs) and environmental samples / Mohamad Hafiz Abdul Basher - Mohamad Hafiz , Abdul Basher (2018)
Acanthamoeba is a ubiquitous free-living protozoa, inhabitants in all environment worldwide. Acanthamoeba infection caused serious diseases of granulomatous amoebic encephalitis (GAE) and acanthamoeba keratitis (AK). This study was to determine the occurrence of Acanthamoeba genotypes in naturally infected corneas of stray cats and dogs and environmental samples. Infected stray cats and dogs from Animal Welfare Society (PAWS) and alleyways (cats only) were identified of having eye infection by the signs of watery eyes, grey discharge and redness. While from the environment, samples were collected from animal bedding, food containers and drinking containers of animals in PAWS, recreational rivers (water, wet debris, soil), children’s playground (soil) and University of Malaya Medical Faculty (indoor and outdoor dust). All samples were subjected to cultivation on non-nutrient agar lawned with Escherichia coli followed by PCR, cloning, sequencing and phylogenetic analysis. Positive culture showed Acanthamoeba trophozoites with spike-like acanthopodia and cysts with wrinkled double thick walled which were detected as early as 2nd and 5 th day, respectively. The occurrence of cultivable Acanthamoeba from corneal samples of both stray cats and dogs was 24.8% (56/225), in which 24% (48/200) in cats and 32% (8/25) in dogs. While from environmental samples, Acanthamoeba was detected at a higher prevalence of 85% (136/160). Phylogenetic analysis revealed that Acanthamoeba isolates in corneas of stray cats and dogs were assemblage under A. castellanii (U07401) genotype T4 with two homologous groups with different bases. For environmental samples, three genotypes were detected (T4, T5 and T15) in PAWS environment, four genotypes (T3, T4, T5 and T15) in recreational rivers, one genotype in dry soil of playgrounds (T4) and two in dust at University of Malaya Medical Faculty (T4 and T15). iv Of the four genotypes (T3, T4, T5 and T15) detected in this study, T4 was found to be the most predominant in infected corneal swabs, soil and dust samples. While genotype T5 was predominant in water samples. Furthermore, genotype T4 was well known to be the main genotype, followed by T3, T5 and T15 in causing human diseases of AK and GAE. The presence of these four genotypes in the environment (water, soil, wet debris and dust) may contribute to Acanthamoeba infection, especially in contact lens wearers and immunocompromised subjects. Rubbing eyes after entering of contaminated soil/dust particles and water during daily activities could lead to eye abrasion, contributing to a high risk of acquiring AK. Furthermore, Acanthamoeba genotype T4 found in infected corneas of stray cats/dogs in this study was possibly due to the entering of soil particles which were highly contaminated with genotype T4. The existence of potential pathogenic genotypes T3, T4, T5 and T15 in the domestic environment can be considered a public health issue. Awareness of Acanthamoeba infections among clinicians is important in order to diagnose AK and GAE in infected patients. Finally, awareness of the health risk on the distribution of Acanthamoeba species in the environment should be made known to the public especially those with high risk of acquiring it. Other than Acanthamoeba, 17.5% (28/160) are other free-living amoebas (FLA) such as Naegleria and Hartmannella species which were detected and were found growing together with Acanthamoeba in the main and sub-culture plates. All of these FLA isolates were subjected to PCR amplification and eight (8) types amplicon size were obtained which were Naegleria species [Type 1 (363 bp), Type 2 (315 bp), Type 3 (315 bp), Type 4 (310 bp), Type 5 (370 bp) and Type 6 (310 bp)] and Hartmannella species [Type 7 (667 bp) and Type 8 (553 bp)]. Naegleria species were found in recreational water samples v and dry soil in playground while Hartmannella species were found in playground dry soil and indoor dust samples at University of Malaya Medical Faculty. All Naegleria species found in this study were not pathogenic to human and to date, pathogenic N. fowleri was not reported from Malaysia. However, there should be awareness on the risk of N. fowleri infection when dealing with water activities such as swimming in recreational natural rivers and Muslims who perform ablution may also be exposed to this FLA that enter via the nostrils. As for Hartmannella more attention should be given in order to know the current status of their existence in the local environment and their ability to associate with other pathogens and cause diseases to humans and animals. Public health education about preventive and control measures on FLA should be given to the community especially when dealing with water activities. Awareness among the medical practitioners and adequate treatment of public water supplies must be emphasized.